Effect of AGEs-RAGE system on the efficacy of PD-1 inhibitors in the treatment of driver-gene mutation negative advanced non-squamous non-small cell lung cancer: Role of AGEs-RAGE in the treatment of NSCLC with PD-1 inhibitors - Li, Xiangying; Wang, Guan; Sun, Xiuye; Feng, Yue; Wang, Lei; Sun, Gangyuan; Qiao, Hong (Cellular and Molecular Biology, 2023)
To observe the therapeutic effect of PD-1 inhibitors on driver-gene mutation negative advanced non-squamous non-small cell lung cancer (nsNSCLC) and the role of the AGEs-RAGE system in the disease, provide more reliable treatment for future nsNSCLC patients. In this study, we selected 130 nsNSCLC patients admitted between January 2021 and April 2022 were selected as the study subjects, 61 of whom received pemetrexed plus carboplatin (control group) and 69 received PD-1 inhibitors, pemetrexed and carboplatin (research group). The clinical efficacy and adverse reactions of the two groups were compared, and the prognostic survival time was calculated. The results show that two groups were not statistically different in objective response rate (ORR) and incidence of adverse reactions, but the disease control rate (DCR) was higher in the research group (P<0.05). Besides, the median progression-free survival (PFS) was prolonged in the research group compared with the control group (P<0.05). In addition, changes in the levels of T lymphocyte subsets, AGEs and RAGE before and after treatment were detected, and the relationship between AGEs-RAGE and the therapeutic effect of PD-1 inhibitors was analyzed. The research group also showed higher CD3+, CD4+ and lower CD8+, AGEs and RAGE levels than the control group after treatment (P<0.05). Finally, we found that in addition, the efficacy of the study group was inversely related to AGEs and RAGE levels (P<0.05). With these results, we concluded that PD-1 inhibitors are effective in the treatment of driver-gene mutation negative advanced nsNSCLC, and the AGEs-RAGE system may provide a more reliable guarantee for the treatment outcomes of patients in the future.